2003
DOI: 10.1177/152660280301000208
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Imaging for Aortic Stent-Graft Surveillance

Abstract: Enhanced ultrasound is a useful method in the long-term surveillance of endovascular aortic aneurysm repairs, possibly in association with CTA or MRA. Enhanced ultrasound also seems able to identify endoleaks missed by other imaging techniques, but this conclusion awaits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 37 publications
(37 reference statements)
1
25
0
Order By: Relevance
“…In the studies included [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], overall sensitivity and specificity were analysed for detection of all types of endoleak in the included 18 studies with a mean follow-up time 8.6 ± 6.4 months in both groups. Data analysis showed higher sensitivity 98% in the CEUS group (p = 0.001) compared with 83% in the CTA group with specificity of 93% in the CEUS group compared with 99% in the CTA group (p = 0.28).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies included [11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], overall sensitivity and specificity were analysed for detection of all types of endoleak in the included 18 studies with a mean follow-up time 8.6 ± 6.4 months in both groups. Data analysis showed higher sensitivity 98% in the CEUS group (p = 0.001) compared with 83% in the CTA group with specificity of 93% in the CEUS group compared with 99% in the CTA group (p = 0.28).…”
Section: Resultsmentioning
confidence: 99%
“…CEUS is a novel alternative technique used in the detection of post-EVAR complications [15]. This imaging modality combines newer generation, non-toxic contrast agents and advanced ultrasound techniques [20]. Early studies suggested that CEUS improves sensitivity and accuracy of detecting endoleaks and classifying them into subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The role and safety of sonographic echo enhancers have already been documented in a study of carotid and aortic stenting, 8,9 indicating their feasibility and accuracy in determining the functioning of endoprostheses at follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Optison™ (Mallinckrodt, St Louis, Mo) was found to accurately classify endoleaks as type 1 or 2, enabling US to detect more endoleaks than delayed-phase CTA [ 38 ]. The diagnostic accuracy of CEUS with Optison™ for the diagnosis of endoleaks is reported at a sensitivity of 100% and specificity of 65% [ 39 ]. CEUS with SonoVue™ has demonstrated variable results, with a sensitivity of 80%–100% and a specificity of 82%–100% in diagnosing endoleaks, outperforming color Doppler US [ 36 , 37 , 40 42 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%